INVESTIGATION OF THE ACCURACY OF DETAILS POSITIONING IN DEVICES WITH ELASTIC GRIP PAWLS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper presents the results of a study of the accuracy of fixing body details on a flat surface and two elastic grip pawls. The obtained experimental results, concerning the displacement of a detail in longitudinal and transverse direction, have been compared with the analytically obtained errors, resulting from positioning a detail on both a cylindrical and a sheared grip pawl. It has been found that the results for the accuracy of details positioning in devices with elastic grip pawls are better than those, related to using a sheared grip pawl and a cylindrical one.